What is Trending in Florida’s Commodity Crops: A Google Trends Analysis: HS1441, 7/2022 - Lee, Tong Geon (EDIS, 2022)
The purpose of this new 3-page article is to briefly discuss the trends of search terms, with an emphasis on Florida’s major crops, that may provide insight into the general public’s interest. With increased knowledge about the interest and perception of the general public regarding Florida crops, Florida’s agricultural industries can better respond to the needs and concerns of consumers. The target audience of this publication includes those involved in agriculture as well as the general public. Written by Tong Geon Lee and published by the UF/IFAS Horticultural Sciences Department.